Colour Studies 2014
DOI: 10.1075/z.191.21ani
|View full text |Cite
|
Sign up to set email alerts
|

Referential meaning in basic and non-basic color terms

Abstract: The chapter presents a linguistic analysis of the referential meanings in the semasiological structure of basic and non-basic color terms in a specific usage situation such as marketing. Although most linguistic studies share the assumption about the central role of the reference-related aspects in understanding the semantic structure of color words, the methods for accessing and operationalizing this type of meaning remain rather limited. We propose that a usage-based bottom-up analysis of referentially-enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…For example, natural kinds (e.g., onions, undyed hair) usually exist only in a few colors, rather than in the full range of a color spectrum, and for these, Steinvall (2002) observed that basic color terms are predominantly used to classify the subtypes based on colors without necessarily being descriptively precise with regard to the actual referent object (e.g., red onion for a purple hue, since there are no other types of onions closer to a prototypical bright red). These results are consistent with Anishchanka, Speelman and Geeraerts's (2014) results from an analysis of color-term usage in online marketing, in which the authors found hypernymous usage with a broad referential range of colors for basic color terms, and a much narrower referential range for non-basic color terms. The exact causal history of basic color terms-whether they arose due to the limited color types in frequently mentioned natural categories, or they just happened to be conveniently adequate for type classification-is, however, admittedly unclear (Steinvall 2002).…”
Section: Further Effects Of World Knowledge Involving Color Termssupporting
confidence: 81%
“…For example, natural kinds (e.g., onions, undyed hair) usually exist only in a few colors, rather than in the full range of a color spectrum, and for these, Steinvall (2002) observed that basic color terms are predominantly used to classify the subtypes based on colors without necessarily being descriptively precise with regard to the actual referent object (e.g., red onion for a purple hue, since there are no other types of onions closer to a prototypical bright red). These results are consistent with Anishchanka, Speelman and Geeraerts's (2014) results from an analysis of color-term usage in online marketing, in which the authors found hypernymous usage with a broad referential range of colors for basic color terms, and a much narrower referential range for non-basic color terms. The exact causal history of basic color terms-whether they arose due to the limited color types in frequently mentioned natural categories, or they just happened to be conveniently adequate for type classification-is, however, admittedly unclear (Steinvall 2002).…”
Section: Further Effects Of World Knowledge Involving Color Termssupporting
confidence: 81%
“…Non-basic colour terminology, often referred to as «non-basic terms» (Anishchanka et al, 2014;Biggam, 2014, p. 9), «fancy name» (Skorinko et al, 2006) or «Elaborate Colour Terms» (Steinvall, 2002) -henceforth ECTs-, could be considered as a more 'sophisticated' one, acquired with time and, especially, with exposure to colour-related contexts (e.g. graphic design, cosmetics, fashion, photography and others).…”
Section: Colour Terminologymentioning
confidence: 99%
“…Non-basic terms present three different types: compositional, consisting of a BCT as head of the compound and premodified by an adjective specifying lightness 3 (e.g. light blue, medium red, dark pink) or its prototypicality (true red, classic red); non-compositional, such as navy, forest, maroon or mauve; and idiosyncratic colour terms, for instance, woodland green, barolo red or summit white, much more marketing oriented (Anishchanka et al, 2014). All of these types sharing a more restricted referential range of colour than BCTs (i.e.…”
Section: Colour Terminologymentioning
confidence: 99%